Perempuan Bali dalam Dunia Politik (Studi Kasus Pemilihan Dewan Perwakilan Rakyat Daerah di Kabupaten Badung Tahun 2009, 2014 dan 2019) - Silaban, Ricard Galyani; Mahyuni, Ida Ayu Putu; Sidemen, Ida Ayu Wirasmini (Humanis; Vol 25 No 4 (2021)DO - 10.24843/JH.2021.v25.i04.p14, 2021)
Balinese Hindu women are said to be laymen in politics. The patriarchal culture that is so strong in Balinese life seems to dictate that a Balinese woman only takes a domestic role and traditional rituals. This study uses the theory of existence and the theory of femenism as a basis for thinking in problems. The research method used is historical methods. The results of the study, namely the struggle of Balinese Hindu women in political activities have increased from 2009, 2014 and 2019, but if calculated globally it is still low. The factor of the involvement of Hindu Balinese women in political activities is the involvement of women in parliament. Political activities have very broad implications, such as having an impact on education, socio-culture, public policy and also having an impact on political activity itself.